1994
DOI: 10.1042/bj3040981
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of thyroid transcription factor 2

Abstract: Thyroid transcription factor 2 binds to the promoters of both thyroglobulin and thyroperoxidase genes, two markers of thyroid tissue differentiation, and its binding modulates the activity of both promoters. In this paper we describe the purification of thyroid transcription factor 2 essentially to homogeneity and demonstrate that it is a thyroid-specific DNA-binding protein. Furthermore, we provide a biochemical characterization suggesting that thyroid transcription factor 2 binds to DNA as a dimer and that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…Recently, it has been shown that expansions of polyA tracts could result in protein misfolding and aggregation, which is toxic for the cells (Caburet et al 2004). Moreover, alanine tracts of some transcription factors have been suggested to be involved in the ability to transactivate or repress the expression of target genes (Civitareale et al 1994;Chadwick et al 1997;Lavoie et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that expansions of polyA tracts could result in protein misfolding and aggregation, which is toxic for the cells (Caburet et al 2004). Moreover, alanine tracts of some transcription factors have been suggested to be involved in the ability to transactivate or repress the expression of target genes (Civitareale et al 1994;Chadwick et al 1997;Lavoie et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…orkhead box E1/thyroid transcription factor 2 (FOXE1, also known as TTF2 or TITF2) is a forkhead/winged helixdomain containing protein (1). FOXE1 was initially characterized as a thyroid-specific transcription factor that binds to both the thyroglobulin (TG) and thyroid peroxidase (TPO) gene promoters, two thyroid differentiation markers (2,3).…”
mentioning
confidence: 99%
“…Degradation of IKB has been suggested to involve ROS, as antioxidants block NF-KB activation, and potent NF-KB activators such as tumor necrosis factor-a, interlukin-1, phorbol 12-myristate 13-acetate (PMA), lipopolysaccharide and okadaic acid all elevate ROS levels (Schreck et al, 1991;Schreck et al, 1992). Redox regulation also has been suggested for the c-myb protooncogene (Guehmann et al, 1992), Ets transcription factor (Wasylyk and Wasylyk, 1993), SP-1 transcription factor (Knoepfel et al, 1994), glucocorticoid receptor (Esposito et al, 1995), early growth response-1 transcription factor (Huang and Adamson, 1993), thyroid transcription factors (Civitareale et al, 1994;Arnone et al, 1995), upstream stimulatory transcription factor (Pognonec et al, 1992), aryl hydrocarbon receptor (Ireland et al, 1995), and estrogen receptor (Hayashi et al, 1997). Oxidants also may stimulate signal transduction by altering ca2+.flux and protein phosphorylation (see ).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%